Board Characteristics and Earnings Management in Chinese Real Estate Industry - ZHOU, Li (2019)
The prime aim of this study is to explore the association between board characteristics and earnings management in Chinese real estate industry during the period ranging from 2009 to 2018. In this study, we use the absolute value of discretionary accruals as the proxy for the level of earnings management. The discretionary accruals are calculated through the modified Jones model. The board characteristics examined are the board size, the percentage of independent directors within the board of directors, the board meetings, the percentage of female directors within the board of directors and the CEO duality. We collect the relevant data from China Stock Market and Accounting Research (CSMAR) database. The information about gender is collected from the annual report. After deleting firms with missing data, the sample size contains 1091 firm-year observations during 2009-2018. Our results find that CEO duality positively affects the level of earnings management while other variables have no significant relationship with earnings management. Therefore, we conclude that reducing the existence of CEO duality could be more effective in constraining the practice of earnings management in Chinese real estate industry. With regards to the control variables, firm size is negatively associated with earnings management while leverage and firm growth have a positive correlation with earnings management. This study contributes to the existing literature on corporate governance and earnings management in Chinese real estate industry by exploring their association.